Sorø i Tvååker - Olsen, Rikke Agnete (Hikuin, 2004)
Sorø at Tvååker By Rikke Agnete Olsen The Cistercian monastery at Sorø on Sealand was kind of family institution for the so-called Hvide family which fostered among other mighty men the archbishops Absalon and Andreas Sunesøn. Absalon endowed the monastery with much land, among that part of Tvååker in Northern Halland to make it possible for them to get timber for their buildings. The gift was not very clearly described; the monks soon came into conflict with the local peasants and Absalons successor and cousins son Andreas Suneson had to specify the quality of the gift. The original documents concerning the transactions are not preserved, but a renewed study of the entry in the Register of the property of the monastery, made at different times but in the middle ages does make it possible to draw the borders of the property and to see that the monks farmed their land and cut their timber. Their lands were close to iron producing areas, but they did not make iron themselves.